Neurophysiology Networks, Plasticity, Pathophysiology and Behavior - Heinbockel, Thomas (IntechOpen, 2022)
This book discusses timely topics in the field of neurophysiology ranging from descriptions of nerve cells and glial cells to neural networks, sensory processing, neuroplasticity, neuropathophysiology, and human behavior. As such, all organizational levels of the nervous system are considered in one or more of the book's twelve chapters. The chapters review or present novel findings and provide the reader with an overview of the current state of the art of neurophysiology research. They discuss research advances in different brain regions and experimental models. In addition, the book contributes to the training of current and future neuroscientists and, hopefully, will lead us on the path to curing some of the biggest challenges in human health.